Comparing the quality of care for long-term ventilated individuals at home versus in shared living communities: a convergent parallel mixed-methods study - Hanna Klingshirn; Laura Gerken; Katharina Hofmann; Peter Ulrich Heuschmann; Kirsten Haas; Martha Schutzmeier; Lilly Brandstetter; Thomas Wurmb; Maximilian Kippnich; Bernd Reuschenbach (BMC, 2022)
Abstract Background People on home mechanical ventilation (HMV) belong to a heterogeneous population with complex care needs. In Germany, outpatient intensive care is provided in people's private home (PH) or in shared living communities (SLC). Increasing patient numbers have led to criticism of the quality of care in recent years. Since quality deficits from the perspective of those affected are largely unclear, the following research question emerged: How do interviews with ventilated individuals and family caregivers explain any differences or similarities in the quality of care between PH and SLC? Methods This study used a mixed-methods convergent parallel design, where quantitative and qualitative components were separately collected and analysed. The quantitative component (structured interviews and online survey) included ventilation characteristics, health-related resource use, health-related quality of life (HRQL) measured with the Severe Respiratory Insufficiency Questionnaire (SRI; range 0-100; higher scores indicated higher HRQL) and the Burden Scale of the Family Caregivers short version (BSFC-s; range 0-30; higher scores indicated higher burden). The qualitative component (semi-structured interviews) focused on people's experience of person-centred care. Data were merged using a weaving method and the Picker framework of Person-Centred Care. Results The quantitative component revealed that ventilated individuals living in PHs were on average 20 years younger than participants living in SLCs (n = 46; PH: 46.86 ±15.40 years vs. SLC: 65.07 ±11.78 years; p = .001). HRQL (n = 27; PH: 56.62 ±16.40 vs. SLC: 55.35 ±12.72; p > .999) and the burden of family caregivers (n = 16; PH: 13.20 ±10.18 vs. SLC: 12.64 ±8.55; p > .999) were not significantly different between living situation. The qualitative component revealed that person-centred care is possible in both care settings (ventilated individuals: n = 13; family caregivers: n = 18). Conclusion This study describes a care situation that is as heterogeneous as the population of people with HMV. HRQL and the burden of family caregivers are highly individual and, like person-centred care, independent of the living situation. Policy decisions that facilitate person-centred care need to recognise that quality of care is highly individual and starts with the free choice of the care setting.